Effect of Obstacle on Deflagration to Detonation Transition (DDT) in Closed Pipe or Channel–An Overview - Sulaiman, S. Z. (Universiti Teknologi Malaysia, 2013)
Due to complicated and rapid process, deflagration-to-detonation transition (DDT) becomes one of the major challenges in combustion theory where the exact mechanism is still poorly understood. Theoretically, the presence of obstacle may disturb flame propagation and hence make the DDT predictions more complex. Thus a comprehensive study is required to acknowledge DDT performance precisely. Lacking of information in literature causes the prediction of the transition period is still uncertain. In contrast, appropriate estimation of the DDT event is crucial for explosion safety. Thus, this present paper discusses the effect of obstacle on prediction transition deflagration to detonation event in pipeline system in order to apply an effective protection and safety systems to prevent and mitigate the gas explosion in industries. In addition the effect of bending on flame acceleration and explosion development would also be explored.